Nye udsmykninger og overhvidtninger: Rumbemalinger i danske kirker, ca. 1100 - ca.1900 - Lillie, Eva Louise (Kirkehistoriske Samlinger, 1995)
One of the subjects to be debated for many years among historians and art historians is the time at which the Danish churches received that white-washed interior that many of them still present today. An examination of a 140 medieval churches in north and northwest Zealand revealed, first, that until about 1600 the character of the decorations was either figurative or ornamental; after 1600 the decorations were almost exclusively ornamental. Second, it is not until the year 1700 has been passed that more than half of the churches present a totally white-washed interior. There are, however, regional, déviances: in north Zealand only 40% of the churches show a white interior whereas it is 75% in northwest Zealand. The allegation that a white-washing of the churches’ interior should have occurred immediately after the Reformation of the Danish church in 1536 and as a result of this is first recorded in 1868. It has since then been repeated innumerable times. Refutations have been published almost as often, but, as the allegation of a connection between whitewashing and Reformation has found expression in a much wider range of publications (among these are newspapers and novels), it has been able to survive regardless of the refutations. The demonstration that it is not until after 1700 that more than half of the churches presented a white interior firmly refutes, however, the allegation of a connection between whitewashing and the Reformation. On the contrary, at all times, there seems to exist a wish for a decorated church.